Pengaruh Sustainability Report Terhadap Kinerja Keuangan Perusahaan Perbankan - Sabrina, Hendro Lukman (Jurnal Paradigma Akuntansi, 2019)
This research aims to obtain empirical evidence about the effect of Sustainability Report toward financial performance. This research uses secondary data obtained from the site www.idx.co.id. The population of this research is banking companies listed in the Indonesia Stock Exchange (IDX) during the year 2014-2016. This research is conducted with a sample of 31 data from banking companies. Furthermore, data collection techniques used in this research is secondary data that is processed using Statistical Package for the Social Sciences (SPSS) ver 25.0 program. The statistical method used to test the hypothesis is the multiple linear regression method. The results of this research show that Sustainability Report has no effect on banking financial performance.